The risk of respiratory symptoms on allergen exposure increases with increasing specific IgE levels. Issue 6 (8th February 2016) - Olivieri, M.; Heinrich, J.; Schlünssen, V.; Antó, J. M.; Forsberg, B.; Janson, C.; Leynaert, B.; Norback, D.; Sigsgaard, T.; Svanes, C.; Tischer, C.; Villani, S.; et al.
Abstract: Background: The relation between IgE sensitization and allergic respiratory symptoms has usually been evaluated by dichotomizing specific IgE levels. The aim of this study was to evaluate the association between specific IgE levels and risk of symptoms on allergen‐related exposure, with special reference to allergen‐related asthma–rhinitis comorbidity. Methods: We considered 6391 subjects enrolled within the European Community Respiratory Health Survey 2, having information on cat/grass/ D. pteronyssinus IgE levels and symptoms on exposure to animals/pollen/dust. The risk of oculonasal/asthmalike/both symptoms was evaluated by a multinomial logistic model. Results: A clear positive association was observed between specific IgE levels to cat/grass/mite and the risk of symptoms on each allergen‐related exposure (test for trend with P < 0.001). This trend was particularly pronounced when considering the coexistence of asthmalike and oculonasal symptoms. Compared to non‐sensitized subjects, subjects with specific IgE to cat >= 3.5 kU/l presented relative risk ratios of 11.4 (95% CI 6.7–19.2), 18.8 (8.2–42.8), and 55.3 (30.5–100.2) when considering, respectively, only oculonasal symptoms, only asthmalike symptoms, or both. A similar pattern was observed when considering specific IgE to grass/mite and symptoms on exposure to pollen/dust. Also the proportion of people using inhaled medicines or visiting a general practitioner for breathing problems in the previous year increased with increasing sum of specific IgE to cat/grass/mite. Conclusion: Specific IgE level is the most important predictor of allergen‐related symptoms. The risk of both oculonasal/asthmalike symptoms increases with specific IgE levels, suggesting that specific IgE contributes to the 'united airways disease'.